Konstitusionalisasi Nilai-Nilai Islam dalam Sistem Hukum Indonesia - Najwa Fakhira Hisbuddin; Halisatul Muslimah; Nur Ramadhani; Kurniati Kurniati (Pusat Riset dan Inovasi Nasional, 2025)
With the largest Muslim population in the world, Indonesia's legal system is based on the 1945 Constitution of the Republic of Indonesia, which does not explicitly define Indonesia as an Islamic state. However, Islamic values such as justice, humanity, deliberation, and public interest are reflected in the constitution and state practices. The purpose of this study is to examine how Islamic values are applied in the Indonesian constitution and in the practice of state governance. The research method used is a qualitative approach. The objective of the study is to understand the relationship and differences between Islamic law and state law through an examination of documents related to legislation, Islamic legal literature, and relevant public policies. The results of the study show that Islamic values serve as a moral and ethical foundation in the formation of national law, although their application faces challenges such as the plurality of legal systems, diversity of society, and social inequality. However, integrating Islamic values substantively, rather than symbolically, can strengthen the nature of national law to be just, humanistic, and responsive to the social dynamics of Indonesian society.